2018
DOI: 10.1016/j.foodres.2018.04.012
|View full text |Cite
|
Sign up to set email alerts
|

Volatile compounds and protein profiles analyses of fermented cocoa beans and chocolates from different hybrids cultivated in Brazil

Abstract: Cocoa beans from different geographical and genetic origins show distinct fermentation dynamics which result in different chocolate qualities. In order to understand the effects of genetic improvement of cocoa plants, in this work volatile compounds and proteins profiles of beginning and end of the fermentation from different cocoa hybrids (CEPEC2004, PH15, PS1319, SJ02) were searched. Moreover, sensorial characterization of the produced chocolate from these hybrids was performed. According to the results obta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(50 citation statements)
references
References 28 publications
0
48
0
2
Order By: Relevance
“…Acids provide unique flavors and are some of the most important precursor substances to synthesize esters, aldehydes, alcohols, and other compounds (Collins, Plh, & Wilkinson, 2003). During the ripening of sufu, acids can originate mainly from lipolysis and proteolysis (Moreira, Vilela, Santos, Lima, & Schwan, 2018). Proteases and lipase are mainly derived from the metabolism of some microorganisms (Ahhmed et al, 2016).…”
Section: Food Chemistrymentioning
confidence: 99%
“…Acids provide unique flavors and are some of the most important precursor substances to synthesize esters, aldehydes, alcohols, and other compounds (Collins, Plh, & Wilkinson, 2003). During the ripening of sufu, acids can originate mainly from lipolysis and proteolysis (Moreira, Vilela, Santos, Lima, & Schwan, 2018). Proteases and lipase are mainly derived from the metabolism of some microorganisms (Ahhmed et al, 2016).…”
Section: Food Chemistrymentioning
confidence: 99%
“…Many studies and numerous publications confirm that cocoa beans are a raw material carrying a powerful load of antioxidants, valued in today's diets mainly for their antiatherogenic, antiradical, and anticancer properties [3][4][5][6]. The genotype of cocoa beans, the region in which they are grown, the environmental conditions, as well as the conditions and parameters of applied technological operations, especially fermentation, drying, roasting, and conching, have a significant influence on the formation of sensory characteristics and antioxidant properties of cocoa bean processing products [7][8][9][10]. As numerous studies have shown, the most degrading content of phenolic compounds is the roasting stage-high-temperature heating of beans or cocoa shots, which significantly affects the antioxidant potential of chocolates [11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the alcohols, the concentrations of ethanol and 1-propanol tended to become lower than that of their counterparts in the control. In contrast, the concentrations of 2-methyl-1-butanol, described as malty and chocolaty [ 39 ], and isoamyl alcohol, described as having the taste of red fruit and framboise [ 40 ], were higher than those of their counterparts in the control. In particular, 2-methyl-1-butanol and isoamyl alcohol were detected at higher concentrations in GUL, DUK, SAN, and SIN samples than in GAL and JOR samples.…”
Section: Resultsmentioning
confidence: 99%